TINJAUAN HUKUM EKONOMI SYARIAH TERHADAP JUAL BELI BUKET UANG DI TANJUNG HILIR PONTIANAK - Halimatus Sa’diyah; Moch Riza Fahmi; Tina Zulfahoirina (Al-Aqad, 2025)
The phenomenon of buying and selling money bouquets in Tanjung Hilir, Pontianak, is increasingly developing as part of the gift-giving trend that prioritizes aesthetic value, uniqueness, and flexibility for various celebratory events. The growing demand for money bouquets raises questions regarding the conformity of this practice with the principles of Islamic Economic Law, particularly concerning price determination and the use of money as an object of transaction. This study aims to describe the practice of buying and selling money bouquets in Tanjung Hilir, Pontianak, and analyze it from the perspective of Islamic Economic Law. This research employs a qualitative method with a normative-empirical approach through data collection techniques such as observation, interviews, and documentation. Data were analyzed using an interactive analysis model, including the stages of data collection, reduction, presentation, and conclusion drawing. The results indicate that the practice of buying and selling money bouquets is conducted both directly and through social media, with the use of real money as part of the bouquet based on mutual agreement between the seller and buyer. Price determination includes components of material costs, the nominal value of the money, and the creative service of the arranger. Based on the analysis of Islamic economic law, this practice is permissible as it does not contain elements of usury (riba), uncertainty (gharar), or gambling (maisir), and the price difference is considered as ujrah or compensation for the arranging service. In conclusion, the buying and selling of money bouquets in Tanjung Hilir, Pontianak, is deemed valid and in accordance with sharia principles as long as it is conducted transparently, fairly, and based on the mutual consent of both parties.